THE SUITABILITY OF DESCRIPTIVE TEXT IN TEXTBOOK OF STUDENT GRADE SEVEN BASED ON CURRICULUM - Natalia Bernita Hutauruk; Berlin Sibarani; Tiarnita Siregar (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2020)
The objectives of this study were to analyze the extent does the presentation of descriptive text in the textbook student grade seven and analyze factors caused the presentation the way it is. The study used qualitative descriptive method. The subjects of this study were two textbooks of student grade seven. The technique of data collecting was byanalyzed using several steps according to Miles’s theory, Huberman and Saldana (2014) analyze data with three steps: data condensation, data display, and conclusion drawing and verification. After analyzing the data, the researcher found the text structure in two textbook is mpt perfect yet. The text structure of descriptive text which is classification in textbook by Kemendikbud is unavailable while in Erlangga, the location in descriptive text is unavailable. But, the components of lexicogrammatical is presented well. The result of the study showed that the reason underlying the imperfectness is financial factor. Erlangga publisher is purpose to gaining a financial benefit, while Kemendikbud publisher is not motivated by the profit.Keywords: descriptive text, textbook, curriculum 2013